2021
DOI: 10.1038/s41598-021-85071-2
|View full text |Cite
|
Sign up to set email alerts
|

Lowest nocturnal systolic blood pressure is related to heavy proteinuria and outcomes in elderly patients with chronic kidney disease

Abstract: Ambulatory blood pressure monitoring (ABPM) can produce many variables, of which the lowest nocturnal systolic blood pressure (LNSBP) currently used in calculating morning surge is occasionally overlooked in recent kidney studies compared with other ABPM parameters. We explored the clinical effects of LNSBP in elderly patients with chronic kidney disease (CKD) in a multicenter, observational cohort study. A total of 356 elderly patients with CKD from 19 clinics were included in this analysis. We used multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…28 A multicenter cohort study of 356 older Chinese patients with CKD showed that proteinuria and kidney progression was associated with the lowest level of nighttime BP. 29 In a crosssectional analysis among 2386 patients with nondialysis CKD, patients with isolated nighttime hypertension had higher odds of target organ damage, including LVH, abnormal carotid intima-media thickness, low eGFR, and albuminuria. 28 Diagnosis of nighttime hypertension relies on ABPM, meaning that nighttime hypertension may often be masked by normal office BP measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 A multicenter cohort study of 356 older Chinese patients with CKD showed that proteinuria and kidney progression was associated with the lowest level of nighttime BP. 29 In a crosssectional analysis among 2386 patients with nondialysis CKD, patients with isolated nighttime hypertension had higher odds of target organ damage, including LVH, abnormal carotid intima-media thickness, low eGFR, and albuminuria. 28 Diagnosis of nighttime hypertension relies on ABPM, meaning that nighttime hypertension may often be masked by normal office BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies in general populations and patients with hypertension and CKD showed that elevated nighttime BP was associated with target organ damage . A multicenter cohort study of 356 older Chinese patients with CKD showed that proteinuria and kidney progression was associated with the lowest level of nighttime BP . In a cross-sectional analysis among 2386 patients with nondialysis CKD, patients with isolated nighttime hypertension had higher odds of target organ damage, including LVH, abnormal carotid intima-media thickness, low eGFR, and albuminuria …”
Section: Discussionmentioning
confidence: 99%
“…CKD results from diverse causes and is characterized by the progressive and irreversible loss of renal function, taking up about 11%-16% of the global population [25,26]. Numerous basic and animal articles have verifed that MRAs are capable of signifcantly suppressing the activity of proinfammatory cytokines and pro-oxidants, improving the antiinfammatory response of kidney tissue, improving renal ischemia, mitigating collagen deposition, and preventing renal fbrosis [2,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Some have demonstrated that absolute nocturnal BP is more important than dipping status. 22,23 Hermida has repeatedly shown that adults with isolated nocturnal hypertension have a higher risk of CKD progression than those with isolated daytime hypertension. 24 Interestingly, this effect was not observed in our population.…”
Section: Discussionmentioning
confidence: 99%